1998
DOI: 10.1182/blood.v91.10.3734.3734_3734_3745
|View full text |Cite
|
Sign up to set email alerts
|

Lyn Physically Associates With the Erythropoietin Receptor and May Play a Role in Activation of the Stat5 Pathway

Abstract: Protein tyrosine phosphorylation plays a crucial role in signaling from the receptor for erythropoietin (Epo), although the Epo receptor (EpoR) lacks the tyrosine kinase domain. We have previously shown that the Jak2 tyrosine kinase couples with the EpoR to transduce a growth signal. In the present study, we demonstrate that Lyn, a Src family tyrosine kinase, physically associates with the EpoR in Epo-dependent hematopoietic cell lines, 32D/EpoR-Wt and F36E. Coexpression experiments in COS7 cells further showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 53 publications
5
35
0
Order By: Relevance
“…We could only detect a maximum increase of 1.23-fold activity in BA/F3 cells expressing bc mutants, possibly due to our experimental conditions or to differences in the cell types used by other investigators. Similar observations have been reported previously by numerous researchers and their inability to detect distinct Lyn activation may also be attributed to the speci®c activation of Lyn bound to the receptor complex, which represents only a small fraction of the total amount of Lyn analysed from whole cell lysates (Chin et al 1998). Alternatively, the rapid turnover of Lyn phosphorylation within the whole cell may contribute to a high background level of Lyn activity.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We could only detect a maximum increase of 1.23-fold activity in BA/F3 cells expressing bc mutants, possibly due to our experimental conditions or to differences in the cell types used by other investigators. Similar observations have been reported previously by numerous researchers and their inability to detect distinct Lyn activation may also be attributed to the speci®c activation of Lyn bound to the receptor complex, which represents only a small fraction of the total amount of Lyn analysed from whole cell lysates (Chin et al 1998). Alternatively, the rapid turnover of Lyn phosphorylation within the whole cell may contribute to a high background level of Lyn activity.…”
Section: Discussionsupporting
confidence: 86%
“…The cytoplasmic membrane proximal region of bc and the erythropoietin (Epo) receptor both share a conserved Box 1 motif. Lyn has recently been reported as interacting constitutively with the Epo receptor (Tilbrook et al 1997;Chin et al 1998). Among these, contradicting results were shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among SRC family kinases, LYN has been characterized to play a major role in B cells (Xu et al, 2005), but recent studies revealed that LYN is also involved in cytokine receptor signalling such as erythropoietin receptor signalling (Tilbrook et al, 1997). LYN physically interacts with the erythropoietin receptor and is proposed to play a role in activation of the STAT5 pathway (Chin et al, 1998). Our findings of ETV6-LYN in this study support the role of the SRC family kinases in the regulation of STAT pathways and implicate active LYN in the alternative pathway for STAT activation in pathological cytokine signalling.…”
Section: Discussionmentioning
confidence: 99%